Penerapan Metode Pembelajaran STAD (Student Teams Achivement Division) Berbantuan Aplikasi Filmora untuk Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran Sejarah Kelas XI di SMAN 1 Cigugur - Putri, Keysha Adilla; Lutfi, Ahmad Fajri (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to increase student learning motivation through the application of the STAD (Student Teams Achivement Division) method using the filmora application as a support. This study uses a quantitative method with a Quasi Experimental approach and a Pretest-Posttest Control Design design implemented in SMA Negeri 1 Cigugur with 308 students. The sample of this research was class XI-1 as the experimental class and class XI-3 as the control class. Data were collected using pretest and posttest questionnaires on learning motivation, observation and documentation. Data were analyzed descriptively quantitatively. The results of the study revealed a significant difference in learning motivation between the conventional method and the STAD method assisted by the filmora application, stated through hypothesis testing with a t-test. The average posttest value of the control class was 74,41, while the experimental class was 80,23 with a difference of 5,82. It is known that the calculated t value of 6,380 is greater than the t table of 1,996 (6,380 > 1,996), so H1 is accepted and H0 is rejected.